Membership Categorization Analysis on Communication Studies: An Essay of Applied Methodology - Andrade Braga, Adriana; Gastaldo, Édison Luis; Depiné Alves Guimarães, Juliana (Brazilian journalism research, 2016)
This paper presents a naturalistic methodological perspective applied to the studies of media communications called Membership Categorization Analysis (MCA). Originally developed for classifying and ordering categories within the framework of natural conversation using sequential analysis (the analysis of turn-taking), we present MCA as a promising methodological approach for analysing media discourses due to its context sensitivity, empirical foundations and its view of communication as a social practice that integrates production, distribution and reception to produce meaning.